Social capital and wellbeing among Australian adults' during the COVID-19 pandemic: a qualitative study - Heidi Green; Ritin Fernandez; Lorna Moxham; Catherine MacPhail (BMC, 2022)
Abstract Background COVID-19 has created global disruption, with governments across the world taking rapid action to limit the spread of the virus. Physical distancing and lockdowns abruptly changed living conditions for many, posing specific challenges of social isolation and lack of connectedness due to being physically and socially isolated from family and friends. Social capital is the bonding of individuals within a society that facilitates and shapes social interactions. The aim of this study was to qualitatively explore the impact that existing social capital has on Australians' experience of lockdowns during the COVID-19 pandemic and the effect this has had on their wellbeing and quality of life. Methods Participants from various socioeconomic areas within Australia were purposively selected to participate in semi-structured interviews conducted via videoconferencing or telephone. Inductive thematic analysis of the data was undertaken. Results A total of 20 participants were interviewed ranging in age from 21 to 65 years, including 50% (n = 10) females, 40% (n = 8) males, 5% (n = 1) non-binary and 5% (n = 1) transgender. Three main themes emerged from the analysis of the data: No person is an island; Social engagement; and Loneliness and isolation. Individuals who resided in low socioeconomic areas, those who lived alone and had reduced social support expressed feelings of poorer wellbeing. Conclusions This study describes the lived-experiences of the influence of the COVID-19 pandemic on Australians' social capital and wellbeing. The findings highlight the need for interventions to increase social support, social cohesion, and social connectedness, especially among Australians from low socioeconomic areas, to enhance their overall wellbeing.